IMPLEMENTATION OF THE CONCEPT OF VALUE COMPARISON IN THE TRADITIONAL GAME OF TEK-PRESS IN THE MATHEMATICS LEARNING PROCESS - Maulinda, Diah Ayu; Sangila, Muhammad Syarwa; Agus, Imaludin; Halistin, Halistin; Safaria, Sri Anandari (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
Implementation is an action or implementation of something that has been prepared carefully. What will be implemented in this study is the mathematical concept contained in traditional text-press games in the learning process. The purpose of conducting this research is to to know the increase in mathematics learning outcomes for class VII students at MTsN 2 Konawe Selatan by implementing mathematical concepts in traditional text-press games in the learning process. The research was conducted in class VII B MTsN 2 Konawe Selatan which was taken using purposive sampling with the consideration that there were many students who had played tek-tekan. Data collection methods consist of observation, and tests. Test scores derived from students' pre-test and post look for the value of the difference or N-Gain then do a hypothesis test using one sample t-test. The results of this study indicate that there is an increase in students' mathematics learning outcomes before and after the implementation of mathematical concepts in traditional text-press games in the material learning process compared to the results of hypothesis testing, namely and with a Sig (2-tailed) value of. In addition, from the N-Gain value it is known that there was an increase in the high category by 6 students (33.33%), the medium category by 9 students (50%), and the low category by 3 students (16.66%).